Construction of Legal Norms Regulations Underlying Medical Decision-Making for Periviabilities in The Framework of Maintaining the Right to Life of Newborn Baby in A Just Way - Sugeng, Willy Gunardi (Dinasti Publisher, 2026)
This study examines the legal gap in regulating medical decision-making for periviable infants, namely infants born at gestational ages where survival outside the womb is very low (generally 22–25 weeks). The main problem arises when there is a dilemma between the medical obligation to perform aggressive resuscitation and the parents' right to determine the best course of action for their child, which often clashes with ethical aspects and regulatory limitations in Indonesia. The research method used is normative juridical with a statutory approach and a conceptual approach. Secondary data is analyzed qualitatively to find the philosophical and legal basis for protecting the right to life of infants. The results of this study indicate that current health regulations do not specify the threshold for medical intervention at infant viability, thereby creating legal uncertainty for medical personnel when making critical decisions. The ideal regulatory construction should be based on the principle of the Best Interests of the Child and the value of justice for newborns. This study recommends the need for the establishment of technical regulations (such as the Ministry of Health Regulation) that regulate national clinical guidelines regarding the threshold of viability, a comprehensive informed consent mechanism, and the establishment of a multidisciplinary hospital ethics committee to ensure the protection of infants' right to life without neglecting their future quality of life.